Construcción de un sistema agroecológico a través de la recolección y siembra de plantas medicinales y aromáticas del cantón Babahoyo de la Provincia de Los Ríos - Puentestar Quishpi, Cintya Johanna (2021)
Research work related to the career of Agricultural Engineering, Agricultural Sciences. The Research is of a descriptive-qualitative design, of a phenomenological type. The fundamental objective of this work is the construction of an agroecological system through the collection and sowing of medicinal and aromatic plants, whose theoretical support was based on the perspective (Luz y Lázara 2012) and ethnobotany (Schultes 1941), the instruments Used were, ecological sustainability test, comparative table of medicinal and aromatic plants as well as ethnobotanical survey applied to a sample of 384 inhabitants corresponding to the parishes of Pimocha, La Unión, Febres Cordero and Caracol.